MM-398 (nanoliposomal irinotecan): emergence of a novel therapy for the treatment of advanced pancreatic cancer. (February 2016) - Carnevale, Julia; Ko, Andrew H
While progress in the treatment of advanced pancreatic cancer has accelerated in recent years, this malignancy continues to have an exceedingly poor prognosis, with no standard of care options beyond front-line chemotherapy. Currently, there are a number of new therapeutic agents in varying stages of clinical development, including molecularly targeted agents, immunotherapies, and modified versions of cytotoxics. MM-398, a novel nanoliposomal formulation of irinotecan, was designed to maximize tumor exposure while minimizing systemic toxicity due to its favorable pharmacokinetic profile. Overall, across multiple clinical trials in multiple disease indications, MM-398 has been shown to have a favorable safety and tolerability profile compared with standard irinotecan. Recent results of the Phase III NAPOLI-1 trial in patients with metastatic pancreatic cancer refractory to gemcitabine-based chemotherapy have shown a significant improvement in overall survival of MM-398 when combined with 5-fluorouracil/leucovorin, compared with 5-fluorouracil/leucovorin alone. This review focuses on the development and pharmacokinetic properties of MM-398, followed by evaluation of its safety and efficacy with a primary emphasis on clinical trials in advanced pancreatic cancer.